Development of complex of interactive tests on mathematics in Adobe Captivate - Ковалева, Екатерина Александровна (Technology audit and production reserves, 2014)
The topic of this article is devoted to computer testing that is one of the most actual problems of pedagogy. Computer test development is one of the most time-consuming tasks that arise every day for professors. The author gives his own algorithmic approach to solving this problem. The uniqueness of this approach to creation of such computer tests consists in using the algorithm given in the article for creation a similar test in any discipline that allows you to use this article as a guide for professors who do not have special education in computer technology. Another important component of computer test is creation a text "scenarios" that have a high degree of validity and reliability. The problem of reliability and validity of specific example of the student group testing results of Simon Kuznets Kharkov National University of Economics is shown in detail in the article. Developed interactive computer test can objectively assess the level of knowledge of students, and its use on personal computer does not require installing any additional software. Automatic calculation of test results reduces a workload of professors, related to spending time on revise of student work. The test has a high degree of validity and reliability.